MacBook Air : portable genius - McFedries, Paul (Portable genius., 2012)
Packed with tips and techniques on everything from getting started with the MacBook Air to taking advantage of all its remote features and accessories, this fun, hip, and portable guide has just what you need to confidently get started with the MacBook Air. In this latest edition, veteran author Paul McFedries covers an assortment of new topics including the new OS X Lion, Intel's latest Sandybridge processor, Thunderbolt, and the backlit keyboard.